British Entrepreneurs and Pre-Industrial Revolution Evidence of Cost Management. - Fleischman, Richard K.; Parker, Lee D. (The Accounting Review, 1991)
Accounting histories have dated the advent of sophisticated cost management from the mid-1880s (Solomons 1952). The scientific management movement is credited with instituting and popularizing cost management techniques. However, it might be suspected that British entrepreneurs of the Industrial Revolution would have developed sophisticated costing techniques earlier, given their significant methodological advances in other economic areas. This article reports the findings from surviving business records of 25 sizeable British industrial firms (mostly in the iron and textile industries) from 1760 to 1850. Substantial evidence of a relatively mature cost management has been found in four major areas of activity: cost control techniques, accounting for overhead, costing for routine and special decision making, and standard costing. Speculations about the motivations for cost management and about specific factors influencing the iron and textile industries are considered. Because the accounting practices of these firms predated the genesis of "the costing renaissance" a century later, our understanding of cost management practices in the Industrial Revolution is augmented by the survey.